GENERAL HISTOLOGICAL CHARACTERISTICS OF LYMPHOID NODULES OF PEYER’S PATCHES OF THE SMALL INTESTINE IN ALBINO RATS AFTER ADMINISTRATION OF A BROAD-SPECTRUM ANTIBIOTIC - V. H. Hryn; Y. P. Kostylenko; K. V. Hryn (Проблеми екології та медицини)
Administration of an antibiotic by any route can cause dysbacteriosis, but its risk is the highest when taken orally, since the drug gets directly into the intestine, affecting microflora. After administration of a broad-spectrum antibiotic, Peyer’s patches of the small intestine of albino rats remained unchanged both topographically and in their total amount. But at the same time, their total area is more than doubled, which, according to our data, becomes possible due to the appearance of a new generation of lymphoid nodules in them. The aim of the research was to study the histological characteristics of lymphoid nodules of Peyer’s patches of the small intestine in albino rats after administration of clarithromycin. 30 mature albino male rats weighing 200.0±20.0 g were involved in the experiment. The antibiotic was administered to the rodents as a supplement to food during their two-meals-a-day feeding. Areas of the small intestine with Peyer’s patches have been studied. Serial paraffin sections have been analyzed using the “Konus” light microscope. Morphometric characteristics of the tissue structures were obtained using the Sigeta X 1 mm / 100 Div.x0.01mm stage micrometer. It has been established that after the course of administration of a broad-spectrum antibiotic (clarithromycin) in the small intestine of albino rats, the topography and total number of Peyer’s patches remain unchanged, while their total area increased by more than twice. This hyperplasia of structured lymphoid tissue in the mucous membrane of the small intestine of animals under the influence of the antibacterial drug occurs due to the appearance of new generations of lymphoid nodules in the Peyer’s patches, among which small, medium and large forms are distinguished, similar to the stages of their development. Each of them is distinguished by its morphological features, primarily, the conversion of the lymphoid-associated epithelium. Therefore, the genetically programmed total number of Peyer’s patches in the small intestine of mature albino rats is constant, whereas the number of lymphoid nodules in them is a variable that depends on the state of the intestinal microbiocenosis.